Relative income poverty rates and poverty alleviation via tax/benefit systems in 49 LIS countries, 1967-2016 - Koen Caminada; Jinxian Wang; Kees Pieter Goudswaard; Chen Wang (Luxembourg Income Study (LIS), 2019)
Most welfare states design their tax/benefit system to combat income poverty. Some countries are more effective in poverty alleviation than others. What can explain these variations in outcomes and effectiveness? And has the redistributive power of different social programs changed over time and across countries? This paper analyzes the effectiveness of social transfers and income taxes in alleviating poverty. We focus on 49 LIS-countries for the period 1967-2016. We compare relative income poverty rates at the levels of market incomes and disposable incomes, that is before and after social transfers and income taxes, in order to analyze the effect of tax and transfer policies in reducing income poverty, i.e. to determine the target efficiency of social transfers. We perform several tests with the most recent data. Finally, we perform several partial analyses by disaggregating poverty rates to socioeconomic and demographic conditions in order to investigate to what extent variations at the social program level (such as old age pensions, child benefits) affect the measured effectiveness of the welfare state in alleviating income poverty. We use micro-data from the Luxembourg Income Study (LIS) to examine household market income poverty and disposable income poverty, the antipoverty effect of social transfers and income taxes, and the underlying social programs that drive the changes. LIS data are detailed enough to allow us to measure both overall poverty reduction, and the partial effects of poverty reduction by several taxes or transfers. We elaborate on the work of Caminada et al (2017, 2018 and 2019). LIS data also allow us to decompose the trajectory of the market income poverty to disposable income poverty in several parts (i.e. 9 different benefits and income taxes and social contributions). The Leiden LIS Budget Incidence Fiscal Redistribution Dataset on Relative Income Poverty (LLBIFR Dataset on Relative Income Poverty 2019) allows researchers and public policy analysts to compare antipoverty effects across developed countries and middle income countries over the last five decades. Research may employ these data in addressing several important issues. Changes (in the generosity) of welfare states can be linked to changes in the antipoverty effects. Best-practices among countries can be identified and analyzed in detail. The LLBIFR on Relative Income Poverty 2019 with its detailed data on income taxes and a large number of individual social benefits offers a rich source of information which may be used by scholars and policy analysts to study the effects of different social programs on economic well-being.
Keywords: H53; H55; I32; 330; welfare states; social income transfers; income poverty; LIS